2005
DOI: 10.1089/apc.2005.19.803
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Medication Errors in a National Medication Error Database

Abstract: Antiretroviral medications have reduced the morbidity and mortality associated with HIV. In contrast to these benefits, medication errors involving antiretrovirals represent opportunities for causing harm. We analyzed 400 medication errors that involved at least one single or combined HIV antiretroviral product that had been reported to a national medication error reporting program (MEDMARX). Our analysis revealed that 3% of the errors were harmful. Most of the errors (45%) occurred in the dispensing phase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…We found that, in total, dose‐related problems (incorrect dose, dose omission, and lack of dose adjustment in patients with renal or hepatic impairment) accounted for 43.3% of all errors. This result is comparable to those of Mok et al [4] and Gray et al [15]…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that, in total, dose‐related problems (incorrect dose, dose omission, and lack of dose adjustment in patients with renal or hepatic impairment) accounted for 43.3% of all errors. This result is comparable to those of Mok et al [4] and Gray et al [15]…”
Section: Discussionsupporting
confidence: 91%
“…We found that, in total, dose-related problems (incorrect dose, dose omission, and lack of dose adjustment in patients with renal or hepatic impairment) accounted for 43.3% of all errors. This result is comparable to those of Mok et al [4] and Gray et al [15] Risk factors associated with a HAART-related error in our study were similar to those found by Mok et al [4]: renal impairment, an atazanavir-containing regimen, and admission by a service other than the infectious diseases service. We also found that receiving a nonnucleoside reverse transcriptase inhibitor was a protective factor.…”
Section: Incorrect Schedule (N 5 3)supporting
confidence: 92%
See 1 more Smart Citation
“…One of the main proposed contributors to this difference is the retrospective nature of most prior studies. 1113 In our investigation, patients were actively tracked on a daily basis from admission until discharge by experienced HIV specialized pharmacists, increasing the sensitivity with which errors were identified and corrected. This unexpectedly high frequency of errors also compromised our subsequent risk factor analysis, since the majority of patients had the outcome of interest, thus making it difficult to discern statistically significant associations in our relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…This study of NRTI prescriptions at a university-based HIV clinic using an EMR found errors in 6% of prescriptions overall and in 31% of prescriptions for patients with renal impairment. Previous studies, conducted among HIV-infected inpatients, have identified nonstandard dosing (i.e., overdosing, underdosing, or incorrect frequency of dosing) as the most common error type and have identified lamivudine as the NRTI most frequently associated with prescribing errors [2][3][4][5][6], compared with the findings in our study that a lack of dose adjustment for patients with renal impairment was the most common error and that didanosine was the NRTI most frequently associated with prescribing errors. Because didanosine was the only NRTI for which all 4 defined error types could occur, the complexity of didanosine dosing, relative to dosing with other NRTIs, might explain the higher risk of errors associated with this drug.…”
Section: Resultsmentioning
confidence: 99%